2019
DOI: 10.1080/08923973.2018.1558235
|View full text |Cite
|
Sign up to set email alerts
|

Tachykinin upregulation in atopic dermatitis

Abstract: Context: Atopic dermatitis (AD) is a chronic, inflammatory, itching skin disorder, which may worsen due to stress, depression and anxiety. Tachykinins may be involved in inflammation signaling as well as they may have a role in stress, depression and anxiety.Objective: This study aimed to measure the expression of tachykinin markers, in the skin of patients with AD, and the correlation of these tachykinins with clinical and psychodemographic parameters. Materials and methods: Twenty-eight adult patients with A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…In biopsies from lesional skin of AD patients, they found an increase in the number of SP-and NKA-positive nerve fibres and NKA-positive mononuclear dermal cells, compared to non-lesional skin. Moreover, the depression score and the number of dermal NK1R-positive cells in lesional and non-lesional skin showed a positive correlation [63].…”
Section: Atopic Dermatitismentioning
confidence: 83%
See 1 more Smart Citation
“…In biopsies from lesional skin of AD patients, they found an increase in the number of SP-and NKA-positive nerve fibres and NKA-positive mononuclear dermal cells, compared to non-lesional skin. Moreover, the depression score and the number of dermal NK1R-positive cells in lesional and non-lesional skin showed a positive correlation [63].…”
Section: Atopic Dermatitismentioning
confidence: 83%
“…A subsequent study by the group investigated the expression of tachykinin markers in AD skin and whether they correlate with clinical and psycho-demographic parameters [63]. In biopsies from lesional skin of AD patients, they found an increase in the number of SP-and NKA-positive nerve fibres and NKA-positive mononuclear dermal cells, compared to non-lesional skin.…”
Section: Atopic Dermatitismentioning
confidence: 99%
“…Studies also found that the increase of substance P is due to the upregulation of the tachykinesia system in the skin of patients with inflammatory atopic dermatitis. 15 Pruritus is a significant symptom of AD. Studies investigating the mechanisms of pruritus in humans and mice have reported substance P to be an important mediator of this symptom.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to NK1R, SP can bind to Mas-related G protein-coupled receptors (MRGPCRs), which are implicated in nociception and itch signaling [140]. Increases in SP expression in serum and lesioned skin and NK1R+ fibers in lesioned skin in patients with AD have been reported [141]. However, a recent study revealed no significant relationship between serum SP levels and AD [142].…”
Section: Neuropeptidesmentioning
confidence: 99%